2003
DOI: 10.1073/pnas.0931263100
|View full text |Cite|
|
Sign up to set email alerts
|

Use of combinatorial genetic libraries to humanize N-linked glycosylation in the yeastPichiapastoris

Abstract: The secretory pathway of Pichia pastoris was genetically re-engineered to perform sequential glycosylation reactions that mimic early processing of N-glycans in humans and other higher mammals. After eliminating nonhuman glycosylation by deleting the initiating α-1,6-mannosyltransferase gene from P. pastoris, several combinatorial genetic libraries were constructed to localize active α-1,2-mannosidase and human β-1,2-N-acetylglucosaminyltransferase I (GnTI) in the secretory pathway. First, >32 N-terminal leade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
212
1
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 328 publications
(218 citation statements)
references
References 25 publications
2
212
1
3
Order By: Relevance
“…Surprisingly, there were also quantitative and qualitative differences in the oligosaccharide compositions of the nonmodified strains. In our untransformed strain (GS115) mainly Man 8-9 GlcNAc 2 and small amounts of Man 10-15 Glc NAc 2 were present (in the size range of 5 to 20 glucose units), whereas Choi et al (11) reported that Man 10 GlcNAc 2 is the smallest glycan. The differences in oligosaccharide composition may have been due to the strains used (GS115 and JC308) or the nature of the expressed glycoprotein.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Surprisingly, there were also quantitative and qualitative differences in the oligosaccharide compositions of the nonmodified strains. In our untransformed strain (GS115) mainly Man 8-9 GlcNAc 2 and small amounts of Man 10-15 Glc NAc 2 were present (in the size range of 5 to 20 glucose units), whereas Choi et al (11) reported that Man 10 GlcNAc 2 is the smallest glycan. The differences in oligosaccharide composition may have been due to the strains used (GS115 and JC308) or the nature of the expressed glycoprotein.…”
Section: Discussionmentioning
confidence: 85%
“…It was speculated that this was due to trimming of the high-mannose structures, which would have resulted in the availability of more substrate for elongation of mannosyltransferases. However, this explanation is speculative, as Choi et al (11) used the same Mns1p signal sequence to direct a Caenorhabditis elegans mannosidase successfully to the ER, resulting in Man 5 GlcNAc 2 on the glycoproteins. The two situations, however, are not completely comparable, because Choi et al worked with a strain with a defective OCH1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The immunogenicity of Pichia-derived proteins is an issue that has attracted interest in the literature with regard to humanizing the glycosylation patterns [2,24]. One group of researchers disrupted the PNO1 gene of P. pastoris, resulting in a reduction of N -liked glycosylation of a recombinant human antithrombin.…”
Section: O-and N-linked Glycosylationmentioning
confidence: 99%
“…N-glycans were released and separated from hLF as described earlier [8,12]. Molecular weight was determined by using a Voyager linear matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) mass spectrometer (Applied Biosystems) with delayed extraction.…”
Section: Maldi-tof Analysis Of Glycansmentioning
confidence: 99%
“…The application of a combinatorial library approach has been essential to generate P. pastoris strains harboring combinations of mannosidases, glycosyltransferases, GlcNAc/Gal transporters, and Gal epimerase [24]. Over the past years we have created a library of glycoengineered P. pastoris strains each capable of displaying defined N-linked glycans at high uniformity [5,8,12,17,24]. This growing library of strains has the potential to allow elucidation of the relationship between specific N-linked glycans and the function of glycoproteins.…”
Section: Introductionmentioning
confidence: 99%